2022
DOI: 10.47470/0016-9900-2022-101-1-47-52
|View full text |Cite
|
Sign up to set email alerts
|

The role of working conditions in the formation of occupational morbidity of workers in metallurgical production

Abstract: Introduction. The working population health is the basis of human capital, which is a factor in the country’s sustainable economic development. The conditions of occupational activity rank first in the structure of health factors of a working person. Materials and methods. The working conditions and the structure of the newly identified occupational morbidity at a metallurgical enterprise located in the territory of the Republic of Bashkortostan are analyzed based on statistical reporting documents on newly es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Рефрактометрия проводилась на автоматическом кераторефрактометре RC-5000 (TOMEY, Japan), офтальмоскопия глазного дна проводилась на щелевой лампе TOMEY TSL-5000 (Tomey, Japan) с помощью линз (Ocular High Mag 78D, Ocular Instruments Inc., USA). Изучаемые диагнозы классифицировались по нозологическим группам глазной патологии согласно МКБ-10 по следующим группам [11,12]: заболевания век, заболевания конъюнктивы и роговицы; различные офтальмологические новообразования; заболевания сосудистого тракта; болезни хрусталика и стекловидного тела, нарушения гидродинамики глаза (внутриглазное давление); заболевания зрительного нерва и сетчатки; аномалии рефракции и прочие болезни органа зрения.…”
Section: оригинальные исследованияunclassified
“…Рефрактометрия проводилась на автоматическом кераторефрактометре RC-5000 (TOMEY, Japan), офтальмоскопия глазного дна проводилась на щелевой лампе TOMEY TSL-5000 (Tomey, Japan) с помощью линз (Ocular High Mag 78D, Ocular Instruments Inc., USA). Изучаемые диагнозы классифицировались по нозологическим группам глазной патологии согласно МКБ-10 по следующим группам [11,12]: заболевания век, заболевания конъюнктивы и роговицы; различные офтальмологические новообразования; заболевания сосудистого тракта; болезни хрусталика и стекловидного тела, нарушения гидродинамики глаза (внутриглазное давление); заболевания зрительного нерва и сетчатки; аномалии рефракции и прочие болезни органа зрения.…”
Section: оригинальные исследованияunclassified
“…Despite massive modernization which is now taking place in the industry, workers employed in it are still exposed to variable adverse occupational factors. They include noise, heating microclimate, industrial dusts, flammable, explosive and poisonous substances, vibration, ultra-sound, electromagnetic radiation as well as substantial physical loads and work in night shifts [1,[5][6][7]. Domestic studies have confirmed a substantial role that belongs to adverse occupational factors at metallurgic production in developing pathologies of various organs and systems [8,9], including upper respiratory mucosa.…”
mentioning
confidence: 99%